Ficha Técnica - Organizadores, Ficha Técnica (Novos Estudos Jurídicos, 2013)
<span style="text-align: left; text-transform: none; background-color: #fbfbf3; text-indent: 0px; letter-spacing: normal; display: inline !important; font: 11px Verdana, Arial, Helvetica, sans-serif; white-space: normal; float: none; color: #111111; word-spacing: 0px;">Ficha Técnica Volume 18 - Nº 1 - 1º Quadrimestre de 2013